1999
DOI: 10.2105/ajph.89.6.927
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Canadian women's mammography rates since the implementation of mass screening programs.

Abstract: OBJECTIVES: This study reports on Canadian mammography rates between 1990, when mass screening programs were launched, and 1994/95. METHODS: Mammography rates from 2 national surveys were compared according to the presence of a provincial screening program. RESULTS: Mammography rates among women aged 50 to 69 years (the targeted group) increased significantly, by 16%; increases were twice as high in provinces with screening programs. Among women in their 40s (nontargeted group), the changes were insignificant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…12 Our results are also concordant with Canadian data where no increase in the number of diagnostic mammographies among women aged 40 -49 was observed. 13 For women aged 50 -69 years, the use of diagnostic mammography was, as expected, significantly lower (1.47%) in the 2 screening regions than in the rest of the counties (3.43%). In the 9 counties without organised screening, the official policy on access to diagnostic mammography had, surprisingly, no impact on the use.…”
Section: Discussionsupporting
confidence: 67%
“…12 Our results are also concordant with Canadian data where no increase in the number of diagnostic mammographies among women aged 40 -49 was observed. 13 For women aged 50 -69 years, the use of diagnostic mammography was, as expected, significantly lower (1.47%) in the 2 screening regions than in the rest of the counties (3.43%). In the 9 counties without organised screening, the official policy on access to diagnostic mammography had, surprisingly, no impact on the use.…”
Section: Discussionsupporting
confidence: 67%
“…30 This concurs with the findings of Gaudette et al who reported that the highest mammography rates were observed in those provinces with well established breast screening programmes 31 and further supported by De Grasse et al who showed that the rise in mammography rates in Canadian provinces with screening programmes was twice that of provinces without screening programmes (20% versus 10%). 32 The participation rates across the province vary greatly from a high of 41% in north western Ontario to a low of 5% in the central eastern part of the province and 9% in Metropolitan Toronto. This may be related to the number of facilities where mammography is available in each region.…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 ] There has been evidence that provinces and territories that initiated programmatic screening early were more effective in reaching the target population. [ 49 ] The programs report on their outcomes nationally and show a high degree of compliance with international standards for cancer detection rates, referral rates and other quality indicators. [ 48 ]…”
Section: Resultsmentioning
confidence: 99%